2016
DOI: 10.1208/s12248-016-9875-4
|View full text |Cite
|
Sign up to set email alerts
|

Joint Model of Iron and Hepcidin During the Menstrual Cycle in Healthy Women

Abstract: Abstract. Hepcidin regulates serum iron levels, and its dosage is used in differential diagnostic of iron-related pathologies. We used the data collected in the HEPMEN (named after HEPcidin during MENses) study to investigate the joint dynamics of serum hepcidin and iron during the menstrual cycle in healthy women. Ninety menstruating women were recruited after a screening visit. Six fasting blood samples for determination of iron-status variables were taken in the morning throughout the cycle, starting on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 41 publications
2
15
0
Order By: Relevance
“…Angeli et al. (2016) showed that iron status varies during the menstrual cycle, and this should thus be considered when using hepcidin as a diagnostic measure for WCA 36 . In the present study, 43 (64.2%) subjects claimed that they had regular menstrual cycles.…”
Section: Discussionsupporting
confidence: 44%
“…Angeli et al. (2016) showed that iron status varies during the menstrual cycle, and this should thus be considered when using hepcidin as a diagnostic measure for WCA 36 . In the present study, 43 (64.2%) subjects claimed that they had regular menstrual cycles.…”
Section: Discussionsupporting
confidence: 44%
“…As hepcidin and iron parameters vary during the menstrual cycle , only healthy male volunteers were included. They were medication‐free, nonsmokers, and they did not have excessive alcohol consumption (i.e., more than 30 g of alcohol per day).…”
Section: Methodsmentioning
confidence: 99%
“…Other areas that should be explored in the future include quantifying the influence of the menstrual cycle and the use of hormonal birth control on iron biomarkers within the context of obesity. For instance, the menstrual cycle has been reported to impact systemic iron homeostasis including hepcidin and serum iron [ 53 ] but blood collection for this study was not timed to the cycle phase. It is unknown how much of the differences or lack thereof in iron markers in the present study could be attributed to the time within the menstrual cycle blood samples were collected.…”
Section: Discussionmentioning
confidence: 99%